2005
DOI: 10.1111/j.1365-2109.2005.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily and seasonal variations in haematological and blood biochemical parameters in the tench, Tinca tinca Linnaeus, 1758

Abstract: The purpose of the present study was to characterize daily variations in haematology and blood biochemistry in healthy male and female tench (Tinca tinca) in the four seasons of the year. Red blood cells, haematocrit and haemoglobin presented a similar daily pro-¢le in spring and summer, with high values during the scotophase. Total and di¡erential types of leucocytes showed signi¢cant daily £uctuations, with a di¡erent pattern depending on the season and/or the type of leucocytes studied. A daily rhythm in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(124 citation statements)
references
References 43 publications
15
102
2
5
Order By: Relevance
“…Nevertheless, it is well known that the total protein, hemoglobin, hematocrit and red blood cell concentration may be used to evaluate the physiological state and immune response of fish (De Pedro et al, 2005). In particular, high hemoglobin and red blood cell counts can serve to indicate good health (Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is well known that the total protein, hemoglobin, hematocrit and red blood cell concentration may be used to evaluate the physiological state and immune response of fish (De Pedro et al, 2005). In particular, high hemoglobin and red blood cell counts can serve to indicate good health (Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Total and differential leucocyte counts are important indices of non-specific defense activities in fish (De Pedro et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results on kutum in this investigation, decreased total protein levels were also observed in kutum (6), Esox lucius (23), and Silurus glanis (24) during reproduction time. Previous studies, on the other hand, reported increased total protein concentrations in the blood plasma of Tinca tinca broodstock before reproduction time (25,26). Blood glucose is a highly variable parameter that is strongly influenced by handling and environmental stresses as well as seasonal variations, nutritional status, and sexual maturity, among other stressors (27).…”
Section: Rivermentioning
confidence: 99%